Biaya Transaksi Eksplisit dan Implisit dalam Usaha Ternak Sapi Perah di Kabupaten Bandung Barat - Litna Nurjannah Ginting; Nunung Kusnasdi; Rachmat Pambudy (Institut Pertanian Bogor, 2018)
The dairy farm in Indonesia are dominated by small-scale farms causing it is difficult to obtain access to market information and raises transaction costs in the provision of fodder, the production process and the sale of milk produced. However, transaction costs tend to be hidden and neglected by the farmer while it can affect the farm profit. The objective of this research was to analyze and calculate the transaction costs faced by dairy farmers, either explicit or implicit transaction costs, using Transaction Cost Analysis (TCA). This research was conducted at West Bandung District and classifying samples based on the scale and the membership in cooperative institutions. The explicit transaction cost include membership fee, the pulses, tips for paramedics, security costs, and sanitation cost of Cooperatives Service Location (TPK). The Implicit transaction cost include information cost due to the price differences of tofu and cassava pulp and the opportunity cost of time in obtaining of feed and marketing the milk. The implicit transaction costs that were payed by the farmer were higher than the explicit transaction cost. Information cost component had the highest proportion of total transaction cost with the percentage of 41.65% in cooperative members and 48.16% in non-cooperation members. The small-scale dairy farmers paid higher transaction cost because transaction cost was a fixed cost. Based on institutional, the transaction cost paid by the cooperation members was lower than that paid by the non-cooperation members even though the difference was not significant. The difference in transaction cost only IDR1.39/L for the farmer with ownership of 1-5 cows and IDR7.09/L for ownership of 6-10 cows.